(untitled) (Research, Society and Development, 2022)
The need to build new buildings led the command of the Tocantins State Military Fire Department to relocate soldiers with training in Civil Engineering, to prepare and approve processes for the construction of barracks and other infrastructure of the corporation, as the existing buildings do not meet the demands of the institution. The technical team is made up of officers and enlisted personnel who are located in different sectors, with no specific sector of projects and works, resulting in diversion of functions, lack of equipment, "software", vehicles and adequate consumables. The processes of public works, unlike private works, must follow the requirements of specific legislation, thus being mandatory the preparation of several technical documents for their approval by control, bidding and inspection bodies; however, these public bodies of the State, responsible for the elaboration of such processes, are not always available to meet the corporation’s demand, which culminates in the risk of losing resources that could be used in new constructions or building maintenance; if the institution does not have a specialized technical sector with such attributions.